Rape issue: the level of perception, knowledge, attitude and acceptance of rape myth / Nur Azira Hamzah … [et al.] - Hamzah, Nur Azira; Nek Zaid, Nik Zahidah; Mohd Amin, Nur Firzanah; Dol Said, Yanni Ariana Fedra; Saari, Izni Syamsina; Muhd Irpan, Hamidah (Faculty of Communication & Media Studies, 2022)
In Malaysia, although there are laws against the practice of rape, unfortunately there are at least five rape cases reported in daily basis. This problem not only lies in the hand of victim or the assailants but also to the whole society in Malaysia. This study employed the quantitative study approach to identify the level of knowledge about rape, the attitude towards rape issues, the acceptance of rape myth and the perceptions towards the raping issue. There were 300 undergraduate students involved in this study using convenience sampling technique. 71.3% of the respondents were degree students while 28.7% of the respondents were diploma students. An online survey was created in Google Forms and distributed through social media such as WhatsApp, Messenger, Twitter and Instagram. The findings revealed that the respondents have a high-level perception of the rape issue that is happening in Malaysia. They are aware based on the knowledge of the rape issue, the attitude towards the rape issue, the acceptance of rape myth and their perception towards rape issue.